IMPLEMENTATION OF SIMPLE, FAST AND LOW-COST PRINCIPLES IN E-SUMMONS WITH THE E-COURT SYSTEM - Dian Latifiani; Yusriyadi Yusriyadi; Agus Sarono; Esmi Warassih Pudjirahayu; Suryo Adi Widigdo; Nur Arif Nugraha (Fakultas Hukum, Universitas Diponegoro, 2023)
Courts are expected to provide various advantages, namely speed, consistency, accuracy, and reliability. The judiciary in Indonesia adheres to a simple, fast, and low-cost trial. The reality in Indonesia is that case resolution is long-winded, expensive, and inefficient. The existence of technological developments brings benefits, especially in the world of justice where the judicial system that was originally based on conventional has shifted to an electronic-based justice system from then a new problem arose. E-Summon, which should make it easier to call parties, does not apply to people who are not familiar with technology. E-Summon is considered ineffective because the e-court system sometimes has errors and is considered long-winded because justice seekers who are not yet technologically savvy are required to have an email, be able to operate it, and must be ready if they get a call. This study examines how to optimize the E-Summons feature in realizing a simple, fast, and inexpensive E-Summons system. settlement of civil cases. The results show that the implementation of E-Summons has not been able to run optimally. The not yet optimal implementation of E-Summons is caused by the legal culture of the community that has not been able to accommodate the implementation of E-Summons. The legal culture of the people who are not used to operating e-mail and the lack of openness of technological insight which is the main capital in the implementation of E-Summons, the implementation of E-Summons has not run optimally.